Powerlessness assessment tool for adult patients - Braga, Cristiane Giffoni; Cruz, Diná de Almeida Lopes Monteiro da (Revista da Escola de Enfermagem da USP, 2009)
The objective of this article is to report the development of a tool to assess powerlessness in adult patients. Theoretical, empirical and analytical psychometric based procedures were applied to develop the tool. The tool was tested in 210 patients for item selection, reliability and validation estimate and it consisted of 12 items in three domains: "Capacity to perform behavior" (alpha=0.845); "Self-perception of decision making capacity" (alpha=0.834); and "Emotional responses to perceived control" (alpha =0.578). The total alpha was 0.799. Criteria validity was estimated by testing the association between the developed instrument and a general statement on control perception (p